1977
DOI: 10.1071/pp9770811
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Root System to Nitrate Assimilation in Whole Cotton Plants.

Abstract: Cotton (Gossypium hirsutum L.) is a species in which most nitrate is assimilated in the green shoot. A physiological role for the small amount of nitrate reductase activity in the roots can be questioned on the basis of relative magnitude. In this investigation, cotton plants were grown on nutrient solutions containing either 1 or 5 mM nitrate, and balance sheets were developed for the transport and metabolism of nitrate and reduced nitrogen in the root and shoot during exponential growth. At either nitrate le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

1980
1980
2001
2001

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…The variation in these percetitages reflects the (so far tmknown) presence or absence, respectively, of shoot NR activity in situ in the dark (cf. Abrol et al, 1983, Radin 1977, Reed et al, 1983, Secondly, the RQ found for roots utilizing nitrate was 0.9 to 1,0 (Tab, 2), These values indicate a low NR activity in the roots, since high rates of nitrate reduction lead to a high RQ, as fotind ie roots of white lupin (Lambers et al 1980) atid in excised roots of barley (Willis and Yemm 1955),…”
Section: Carbon Dioxide Measurementsmentioning
confidence: 99%
“…The variation in these percetitages reflects the (so far tmknown) presence or absence, respectively, of shoot NR activity in situ in the dark (cf. Abrol et al, 1983, Radin 1977, Reed et al, 1983, Secondly, the RQ found for roots utilizing nitrate was 0.9 to 1,0 (Tab, 2), These values indicate a low NR activity in the roots, since high rates of nitrate reduction lead to a high RQ, as fotind ie roots of white lupin (Lambers et al 1980) atid in excised roots of barley (Willis and Yemm 1955),…”
Section: Carbon Dioxide Measurementsmentioning
confidence: 99%
“…NRA assayed in vivo without additional NO − 3 best approximated NO − 3 assimilation rates in situ in cotton ( G. hirsutum ) (Radin et al, 1975). Consequently, this assay was used to study regulation of NO − 3 assimilation in cotton (Radin et al, 1975; Radin, 1977) and to determine the partitioning of NO − 3 between shoots and roots in most legume (Andrews et al, 1984) and grass (Andrews et al, 1992; Jiang and Hull, 1999) species. Further, the NRA assay in vivo has been suggested for use as a tool in monitoring systems that determine the changes of N concentration in cotton leaves (Chu et al, 1989).…”
mentioning
confidence: 99%
“…A maioria das espécies herbáceas, incluindo importantes culturas econômicas, reduzem nitrato tanto nas raízes como nas folhas. Em culturas como o algodão (RADIN, 1977), cevada (CHANTAROTWONG et ai., 1976;ASLAM & HUFFAKER, 1982;LEWIS et ai., 1982), soja (CRAFTS-BRANDNER & HARPER, 1982) e milho (HAGEMAN & FLESHER, 1960;WALLACE, 1973), os níveis de redutase de nitrato são mais altos na parte aérea do que nas raízes. Em outras espécies, como girassol (WEISSMAN, 1972), tremoço e rabanete (PATE, 1980), as raízes apresentam atividade bem maior do que a das folhas.…”
Section: Introductionunclassified